2016
DOI: 10.1021/acsami.6b05559
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Branched TiO2 Architectures in Controllable Bloom for Advanced Lithium-Ion Batteries

Abstract: Three-dimensional branched TiO2 architectures (3D BTA) with controllable morphologies were synthesized via a facile template-free one-pot solvothermal route. The volume ratio of deionized water (DI water) and diethylene glycol in solvothermal process is key to the formation of 3D BTA assembled by nanowire-coated TiO2 dendrites, which combines the advantages of 3D hierarchical structure and 1D nanoscale building blocks. Benefiting from such unique structural features, the BTA in full bloom achieved significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…On the other hand, the in situ synthesis has been proven to be a promising method to avoid this problem. Wang et al demonstrated a facile one‐pot strategy to synthesize branched TiO 2 architectures, the reversible specific capacity, and rate performance was remarkably enhanced for LIBs. Previously, our group fabricated branched TiO 2 nanofibers via an in situ preparation method, which also possessed excellent Li + storage performance …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the in situ synthesis has been proven to be a promising method to avoid this problem. Wang et al demonstrated a facile one‐pot strategy to synthesize branched TiO 2 architectures, the reversible specific capacity, and rate performance was remarkably enhanced for LIBs. Previously, our group fabricated branched TiO 2 nanofibers via an in situ preparation method, which also possessed excellent Li + storage performance …”
Section: Introductionmentioning
confidence: 99%
“…To date, a variety of techniques derived from the epitaxial growth have been developed to prepare hierarchically branched TiO 2 (HB‐TiO 2 ) nanostructures, which tolerated some of abovementioned disadvantages, to some extent. On the other hand, the in situ synthesis has proven to be a promising alternative that was capable of circumventing such defects; consequently, the products displayed satisfactory performance in diverse fields . Wang et al prepared branched TiO 2 architectures by the in situ hydrothermal process, and this nanomaterial displayed improved reversible specific capacity and rate performance as anode for Li‐ion batteries, attributing to its high surface area and the short migration distance for Li + ion/electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al prepared branched TiO 2 architectures by the in situ hydrothermal process, and this nanomaterial displayed improved reversible specific capacity and rate performance as anode for Li‐ion batteries, attributing to its high surface area and the short migration distance for Li + ion/electrons. [13a]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations